Black disability politics - Schalk, Samantha Dawn (Duke University Press, 2022)
"In Black Disability Politics Sami Schalk explores how issues of disability, broadly construed, have been and continue to be incorporated into Black activism, from the 1970s to the present. In so doing, she establishes a new lineage for disability politics, one that allows the work of contemporary Black disability justice activists to be central. Aiming to speak to both academic and activist audiences, Black Disability Politics identifies common qualities of Black disability politics and provides praxis-based approaches for enacting these politics in contemporary social justice work. Using the archives of the Black Panther Party and the National Black Women's Health Project alongside interviews with contemporary Black disabled cultural workers, Schalk argues that the work of Black disability politics not only exist, but are essential to the future of Black liberation movements"--